2016
DOI: 10.1002/2015gl067325
|View full text |Cite
|
Sign up to set email alerts
|

Time scales of the European surface air temperature variability: The role of the 7–8 year cycle

Abstract: Air temperature variability on different time scales exhibits recurring patterns and quasi‐oscillatory phenomena. Climate oscillations with the period about 7–8 years have been observed in many instrumental records in Europe. Although these oscillations are weak if considering their amplitude, they might have nonnegligible influence on temperature variability on shorter time scales due to cross‐scale interactions recently observed by Paluš (2014). In order to quantify the cross‐scale influence, we propose a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
4
18
0
2
Order By: Relevance
“…In particular, these findings are consistent with the global presence of the 7-8-yr mode in the interannual climate variability for the North Atlantic, North America, Europe, and Eastern Africa (see e.g. Kondrashov et al 2005;Hanrahan et al 2009;Feliks et al 2013;Jajcay et al 2016). …”
Section: A Wind-stress Modessupporting
confidence: 77%
See 1 more Smart Citation
“…In particular, these findings are consistent with the global presence of the 7-8-yr mode in the interannual climate variability for the North Atlantic, North America, Europe, and Eastern Africa (see e.g. Kondrashov et al 2005;Hanrahan et al 2009;Feliks et al 2013;Jajcay et al 2016). …”
Section: A Wind-stress Modessupporting
confidence: 77%
“…Interannual oscillatory modes in the North Atlantic region in both the ocean and the atmosphere have been identified in many observational studies (e.g., Bjerknes 1964;Deser and Blackmon 1993;Dettinger et al 1995;Hurrell and Van Loon 1997;Moron et al 1998;Da Costa and Colin de Verdière 2002;Feliks et al 2010;Jajcay et al 2016). The extent to which these oscillations are due to purely oceanic Berloff et al 2007, and references therein), purely atmospheric (Frankignoul and Hasselmann 1977;Frankignoul et al 1997) or coupled (Vannitsem et al 2015, and references therein) processes is still a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…For L 2  = 7.5 years, oscillations with a period of about 7–8 years have been observed in some instrumental records in Europe, including the CET record2122. Recently, by quantifying the cross-scale information transfer, it has been shown that the effect of this 7–8-year cycle can influence the interannual variability of air temperature anomalies2324. This result is in contrast to the results of Yang16, in which the scale signal at 65.8 years was thought to be the AMO signal; however, in this study, a similar scale signal at 67.7 years is regarded as a harmonic of the solar cycle due to the approximately harmonic relationships.…”
Section: Resultsmentioning
confidence: 99%
“…SFA is a method for extracting slowly varying driving forces from a quickly varying time series. This method has been applied to nonstationary time series with some success and can be applied to nonstationary time series to estimate a single underlying driving force with high accuracy242526. The details of SFA can be found in literature (Wiscott, 2003)9.…”
Section: Methodsmentioning
confidence: 99%
“…Detection of information transfer from instrumental and model climate data helps to shed new light on the known climate processes as well as to uncover new phenomena such as the recently observed information transfer across time scales of atmospheric dynamics 31 which has a considerable impact on interannual temperature variability. 32 …”
Section: Discussionmentioning
confidence: 97%